Organizational adaptation to interdependence shifts: The role of integrator structures - Stan, Mihaela; Puranam, Phanish (Strategic Management Journal, 2017)
R esearch summary: We investigate how organizational adaptation to interdependence shifts is influenced by “integrators.” These are formally mandated managerial roles meant to promote coordination across specialized but interdependent organizational subunits, yet they do so without relying on formal authority. While much has been learned about how integrators promote steady‐state coordination within a known pattern of interdependence, less is known about their impact on organizational adaptation when the pattern of interdependence itself is unknown. We discuss mechanisms by which integrators may nonetheless aid organizational adaptation and learning processes in such situations, and test our hypotheses in the context of a regulatory change that affected the in vitro fertilization ( IVF ) clinics sector in the United Kingdom using a differences‐in‐differences design . M anagerial summary: Organizational structure can influence how an organization adapts to change. We investigate how a regulatory change in the provision of fertility treatments in the United Kingdom forced clinics to change their workflows, and whether the presence of integrator roles enabled clinics to adapt to these changes. It is well known that integrator roles in general are valuable in coordinating across specialized organizational units, but this research points to the surprising implication that their value may persist even when the workflow being coordinated changes suddenly, in ways that nobody necessarily comprehends. Our research highlights the fact that even in an intensively science‐based work context, the “technology of organizing” can have a significant role in shaping organizational performance . Copyright © 2016 John Wiley & Sons, Ltd.